RETRACTED: Rainbow trout MRC structures - Golotin Vasily; Dong Xiangli; Rozhkovan Konstantin; Li Jiji; Ye Yingying (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001